EFFECT OF REMOVABLE ORTHODONTIC APPLIANCES ON THE PEDIATRIC PATIENT'S ORAL HEALTH AND MICROBIOTA: A SYSTEMATIC REVIEW (CAHIERS MAGELLANES-NS, 2025)
This systematic review examines the effects of removable orthodontic appliances (ROAs) on the oral health and microbiota of pediatric patients. Eight studies focusing on microbial colonization, biofilm formation, and oral health impacts were analyzed. The findings indicate that ROAs create a favorable environment for the growth of cariogenic bacteria, such as Streptococcus mutans and Lactobacillus, and for fungal species like Candida albicans. Biofilm formation was prevalent on appliance surfaces, with significant colonization of anaerobes, Enterobacteriaceae, and other pathogenic microorganisms. These microbial shifts correlate with increased dental plaque, Approximal Plaque Index (API), and risk of gingivitis. Additionally, pediatric patients experienced adverse impacts on oral health-related quality of life, including discomfort and halitosis, which are attributed to microbial imbalances and inflammation. This review highlights the need for enhanced hygiene protocols and regular monitoring of microbial health in pediatric patients using removable orthodontic appliances.